Sistem Penguburan Terlipat Takengon: Tambahan Data Baru Penguburan Dalam Gua di Indonesia - Taufiqurrahman Setiawan (Balai Arkeologi Sumatera Utara, 2011)
AbstractArchaelogical data about prehistoric burial inside of prehistoric cave or rock-shelter site in Indonesia has been found in some sites that spread at some different provinces, such as Central Java, West Java, East Java, East Borneo, and also South Sumatra. Now, there is addition one that found in Loyang(cave) Mendale and Loyang Ujung Karang in Takengon, Central Aceh, Nanggroe Aceh Darussalam.